2017
DOI: 10.1097/mib.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Symptoms of Methotrexate Intolerance in Pediatric Inflammatory Bowel Disease

Abstract: Symptoms of MTX intolerance are frequent in pediatric IBD. The Methotrexate Intolerance Severity Score questionnaire could help better recognition of these symptoms. Identification of risk factors could have important implications for the success of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
11
3
Order By: Relevance
“…It has even been proposed that antiemetic medicine should be introduced very early in order to avoid the development of a conditioned response–i.e. anticipatory nausea [23,24]. Supported by Dupont-Lucas et al [24] who found that children with inflammatory bowel disease receiving antiemetic medicine secondarily, compared to prophylactic, were more likely to be MTX intolerant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has even been proposed that antiemetic medicine should be introduced very early in order to avoid the development of a conditioned response–i.e. anticipatory nausea [23,24]. Supported by Dupont-Lucas et al [24] who found that children with inflammatory bowel disease receiving antiemetic medicine secondarily, compared to prophylactic, were more likely to be MTX intolerant.…”
Section: Discussionmentioning
confidence: 99%
“…anticipatory nausea [23,24]. Supported by Dupont-Lucas et al [24] who found that children with inflammatory bowel disease receiving antiemetic medicine secondarily, compared to prophylactic, were more likely to be MTX intolerant. Once anticipatory and associative symptoms are present a psychological intervention–e.g.…”
Section: Discussionmentioning
confidence: 99%
“…106 In a retrospective study, 31% of 102 pediatric patients with IBD experienced methotrexate intolerance (gastrointestinal or behavioral symptoms). 110 Strategies to reduce these effects in children have been reported. 111 Other adverse events included elevated liver function tests, headache, and hematologic toxicity.…”
Section: Recommendation Statementsmentioning
confidence: 99%
“…Recently two large studies on anti-emetics for MTX-intolerance in pediatric patients have been published, providing some evidence against the conclusion by Falvey et al [ 4 , 5 ]. Scheuern et al described the results of a prospective, observational study in 196 JIA patients.…”
mentioning
confidence: 99%
“…Dupont-Lucas et al performed an observational study in 102 pediatric IBD patients. They concluded: “Prophylactic prescription of anti-emetics (…) did not prevent symptoms of MTX intolerance” [ 5 ]. Both studies were not randomized, so firm conclusions cannot be drawn from these studies either.…”
mentioning
confidence: 99%